PENINGKATAN PENGETAHUAN TEKNIK BUDIDAYA DAN USAHA PEMBIBITAN JABON MERAH OLEH KTH MAKMUR LESTARI - Tuheteru, Faisal Danu (Jurnal Dedikasi Masyarakat, 2020)
This article aims to reveal the knowledge and mastery of cultivation technology and red jabon breeding by members of the forest farmer group (KTH) Makmur Lestari. The method for obtaining data was carried out by means of a pre-test and post test on 30 KTH members as participants in the Cultivation Technical Guidance and Guidance and red jabon business analysis which was carried out on 23-24 August 2019 in Andinete village, Kolono sub-district, South Konawe. The test results showed that overall the participants knew exactly about Red Jabon and its economic prospects. Apart from that, there was a significant increase in knowledge and mastery of red jabon cultivation technology between before and after counseling and technical guidance. There was an increase of around 77% of participants being able to calculate the analysis of the Red Jabon breeding business. Increasing the capacity of forest farmers needs to be done through extension and technical guidance.